Concentrate management in desalination : case studies - Tansel, Berrin; Keyes, Conrad G.; Nava, Luzma F.; Lander, April J. (Geotechnical special publication ;, 2021)
"This report reviews the state-of-the-practice for managing the concentrate streams resulting from desalination processes"--